1966
DOI: 10.1002/jsfa.2740170207
|View full text |Cite
|
Sign up to set email alerts
|

Field experiments on the magnesium requirement of cereals, potatoes and sugar beet in relation to nitrogen and potassium application

Abstract: Birch et al.: Magnesium Requirements of CropsAbsorbance was measured on a Unicam SP500 spectrophotometer. Chromatograms were repeated several times : the results are as follows : Extract Method 1 1 2 2 PC TLC PC TLC No. of chromatograms 5 5 4 4 Mean absorbance at 500mp 0.621 0.601 0.986 0,985 R.m.s. deviation 0.009 0.010 0.030 0.012 Coefficient of variation 1 . 5 1 . 6 3.1 1 . 3 %In a series of 14 assays, each performed in triplicate by TLC, the coefficient of variation was in the range 0.3-3.2 %, with a mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

1972
1972
1977
1977

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…There was a general lack of effect from applied Mg, confirming the findings of Holmes (1962), Birch et al (1966), Edwards (1967) and others.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…There was a general lack of effect from applied Mg, confirming the findings of Holmes (1962), Birch et al (1966), Edwards (1967) and others.…”
Section: Discussionsupporting
confidence: 87%
“…Application of very high rates of potassium (300-350 kg K/ha) in the same experiments depressed yield compared with a normal rate (150 kg K/ha). Birch, Devine & Holmes (1966), in 14 experiments, found little effect of 29 kg Mg/ha applied to the seed bed on potato yield. Edwards (1967), Laughlin (1966) and Peeler & Heafield (1966) confirmed that there are negligible responses to applied magnesium sulphate.…”
mentioning
confidence: 93%
“…Only a very low magnesium content in the growth base limited the yield (Jokinen 1977). In several experiments (Vigerust 1966, Birch et al 1966, Sorteberg 1975) the conclusion has been reached that magnesium fertilization does not affect the yield of cereals, but increases the magnesium content of the plants. In these experiments, carried out on mineral and peat soils, the magnesium content of the growth base was probably not so low as to retard the growth of the crop.…”
Section: Discussionmentioning
confidence: 98%